Two-Channel System With Brightness Amplification for Monitoring the Combustion of Aluminum-Based Nanopowders; IEEE Transactions on Instrumentation and Measurement; Vol. 70 - Gubarev F. A. Fedor Aleksandrovich; Burkin E. Yu. Evgeniy Yurievich; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Li Lin (2021, 2021)
Title screen